2012
DOI: 10.1186/1472-698x-12-13
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of teenagers and older pregnant women in the utilization of prevention of mother to child transmission [PMTCT] services in, Western Nigeria

Abstract: IntroductionMost HIV/AIDS infections in women occur at a younger age, during the first few years after sexual debut. This study was therefore designed to assess factors associated with the knowledge and utilization of the prevention of mother-to-child transmission (PMTCT) services by the teenage pregnant women when compared to mature pregnant women in Ogun state, Nigeria.MethodsThis study is an analytical cross-sectional study. A total sample of all pregnant women [52 teenagers and 148 adults] attending the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…This finding is consistent with the study conducted in Dire Dawa, East Ethiopia, in which older age groups (30 years and above) were more likely to accept VCT as compared to those younger (19 years and below) [16] and in Gondar, northwest Ethiopia, in which 15-24 aged mothers were 5.6 more likely to accept PITC in the ANC clinics [13]. But a study conducted in Debre Markos, north-west Ethiopia, reported that sociodemographic variables showed no association [17] and another study conducted in Nigeria showed teenagers were 3 times less likely to utilize the service when compared with the older women [18]. This could be that younger and older women may differ in their perceived risk of HIV and understanding of the importance of HIV testing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is consistent with the study conducted in Dire Dawa, East Ethiopia, in which older age groups (30 years and above) were more likely to accept VCT as compared to those younger (19 years and below) [16] and in Gondar, northwest Ethiopia, in which 15-24 aged mothers were 5.6 more likely to accept PITC in the ANC clinics [13]. But a study conducted in Debre Markos, north-west Ethiopia, reported that sociodemographic variables showed no association [17] and another study conducted in Nigeria showed teenagers were 3 times less likely to utilize the service when compared with the older women [18]. This could be that younger and older women may differ in their perceived risk of HIV and understanding of the importance of HIV testing.…”
Section: Discussionmentioning
confidence: 96%
“…Among the sociodemographic variables, age of mothers was significantly associated with utilization of PMTCT service. Older women (25-34) were 54% less likely to utilize PMTCT service as compared to younger ones (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). This finding is consistent with the study conducted in Dire Dawa, East Ethiopia, in which older age groups (30 years and above) were more likely to accept VCT as compared to those younger (19 years and below) [16] and in Gondar, northwest Ethiopia, in which 15-24 aged mothers were 5.6 more likely to accept PITC in the ANC clinics [13].…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is a proposition and the extent to which it is true needs to be ascertained by future studies. Adolescents are a high risk group for HIV transmission 19 and MTCT risk is very high regarding incidents of HIV infection in pregnancy. 19 It was notable in this study that the adolescent age group did not have an association with PMTCT programme uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents are a high risk group for HIV transmission 19 and MTCT risk is very high regarding incidents of HIV infection in pregnancy. 19 It was notable in this study that the adolescent age group did not have an association with PMTCT programme uptake. Adolescent reproductive health needs should be prioritised in PMTCT approaches to ensure the success of the elimination of MTCT agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported that sociodemographic factors like age [9], urban living [10], higher educational level [11], and being house wife [12] as factors that affect mothers' knowledge of MTCT of HIV. Studies conducted in southern and northwest Ethiopia [10, 12, 13] reported that gravidity, parity, antenatal care (ANC) visits, and male partner discussion are factors associated with good knowledge of mothers on MTCT of HIV.…”
Section: Introductionmentioning
confidence: 99%